(untitled) (International Journal of Engineering and Computer Science, 2022)
Every person has a unique finger vein pattern existing within each finger. Unlike facial features or fingerprints, finger vein authentication systems aren’t vulnerable to forgery. Finger vein authentication systems are more secure and reliable, and less expensive, than biometric security systems using fingerprint. This paper presents a novel security framework based on finger vein pattern. Finger Vein pattern in used in ID based cryptography to generate the keys for data encryption. These keys are combined with generator of Elliptic Curve Cryptography (ECC) to exchange the keys using Diffie Hellman key exchange algorithm. Once the keys are exchanged, the data is encrypted using Advance Encryption Standard (AES). This framework is tested in Internet of Things (IoT) environment for enhancing the security. The IoT based security systems implemented in the banks and other organizations can be enhanced considerably using the proposed security model.